Optimization of Bus Stops, New Pick-up and Drop-off Locations for Public Transportation - Martins Monteiro, Cristiano; Cruzeiro Martins, Flávio Vinícius; Davis Jr, Clodoveu Augusto (Journal of Information and Data Management, 2018)
The increase in urban population, together with the expansion of cities, has motivated the study of improvements for dynamics aspects of daily urban life. An important portion of these dynamic aspects is related to the population’s routine activities, like commuting using public transportation. This work proposes two meta-heuristics and one integer programming modeling to analyze the location of bus stops and propose new pick-up and drop-off locations in order to avoid long walks to take the bus. A real dataset of the road network was integrated to the location of bus stops in the city of Belo Horizonte. Computing approaches were proposed to optimize the location of bus stops in a scalable way. Experimental results show that many new bus stops are required to improve the quality of the service rendered to the population.